DAYA BUNUH EKSTRAK DAUN TOMAT (Solanum lycopersicum L.) TERHADAP LARVA NYAMUK Aedes aegypti - Setyo Dwi Santoso; Abdul Chamid; Dwi Viddi Kusuma Pratiwi (Jurnal SainHealth, 2018)
Dengue hemorrhagic fever (DHF) is a very dangerous disease, caused by Aedes aegypti mosquitoes. One alternative to controlling Aedes aegypti mosquitoes is to use insecticides. But it would be much better if the insecticides used are natural and environmentally friendly, one of them by using Tomato Leaf Extract (Solanum lycopersicum l.). Tomato leaves contain chemical compounds class Alkaloids and Saponins and can serve as anti larvacide. This research is a laboratory experiment which aims to find out the effect of tomato leaf extract (Solanum lycopersicum L.) activity on the death of III instar larvae of Aedes aegypti mosquito. the effectiveness of samples on Aedes aegypti mosquito larvae by treatment of variation of extract concentration 0.2%, 0.4%, 0.6%, 0.8%, 1% with repetition 2 times. In the results of research showed that the smallest concentration that can kill Aedes aegypti mosquito larvae is 0.6% at 16 hours and probit analysis showed that significance is 0,608 greater than intercept 0.003, it shows that the extract of tomato leaves affects the death of III instar larvae of Aedes aegypti mosquito.